A study review on mechanical properties of polylactic acid (PLA) with plasticizer vegetable based and composite material - Mohd Hanafi, Mohd Hafidzal; Jefri, Ernie Suryati; Razak, Nurul Hanim; Abdul Manaf, Muhammad Zaidan; Md Yusof, Fahmi Asyadi; Suhaimy, Syazwan Hanani Meriam; Grasianto (The Italian Association of Chemical Engineering, 2025)
Polylactic Acid (PLA) has received considerable attention worldwide due to its ability to act as biodegradable material that has a lot of similarity towards petrochemically derived products. However, PLA still experience drawbacks such as high brittleness and low toughness that require further research. These limitations can be addressed through plasticization, polymer blending and crosslinking mechanism. The incorporation of vegetable oil-based plasticizer in PLA has been found to enhance its mechanical properties due to high lubricity, high index viscosity and good solvency characteristic. These contributes to increase in ductility, tensile strength, stability and toughness. In parallel, addition of composite materials further strengthens PLA by redistributing stress from polymer matrix to reinforcing phases and improving interfacial adhesion. This review emphasis on the effect of plasticizer and composite material in modifying PLA mechanical properties focusing on tensile strength, flexural strength and elongation at break, while other aspects are reserved for future studies. The aim is to advance PLA as a sustainable material with performance comparable to petrochemically derived product. Plasticizer that being discussed in this review are epoxidized jatropha oil (EJO), epoxidized chia seed oil (ECO), epoxidized soybean oil (ESO), epoxidized palm oil (EPO) and epoxidized waste cooking oil (EWCO). Meanwhile, composite material reviewed are kenaf fibre, zinc oxide nanoparticles (ZnO NPs), and 3- amino phenylboronic acid (APBA). The results showed that EPO promotes stronger hydrogen bonding within the PLA matrix due to higher oxirane oxygen content, thereby increase the tensile strength efficiently. The study also revealed that APBA helps to form borate ester linkage through interaction between boric acid groups and hydroxyl groups in PLA, that contributes to higher elongation at break. ZnO NPs additions introduce new functional properties which is antibacterial traits, while increasing tensile strength. The ability of epoxy group in EWCO to insert themselves between PLA chains helps to reduce van der Waals and hydrogen bonding, that leads to increase in flexural strength. This paper present findings on the effect of vegetable oil-based plasticizer and composite material towards PLA mechanical performance for wider applications as a sustainable product.